Respuesta :

the answer to the question above is  c (2,5) u were correct

Answer:

The solution is (2,5)      

Step-by-step explanation:

Given the two equations

[tex]y-3=x [/tex]

[tex]x^2-6x+13=y [/tex]

we have to find the solution of the above two equations.

[tex]y-3=x [/tex] ⇒ [tex]y=x+3[/tex]

[tex]x^2-6x+13=y [/tex]

Substituting value of y

[tex]x^2-6x+13=x+3[/tex]

[tex]x^2-7x+10=0[/tex]

[tex]x^2-5x-2x+10=0[/tex]

[tex]x(x-5)-2(x-5)=0[/tex]

[tex](x-5)(x-2)=0[/tex]

x=5 or x=2

when x=2, y=2+3=5

Hence, the solution is (2,5)

Option C) is correct.